Protestant anthropology: between secularity and postsecularity - Gavryliuk, Tetiana (Ukrai͏̈ns'ke relihijeznavstvo, 2015)
Protestant anthropology: between secularity and postsecularity. In this article the analysis of main problems of the Protestant anthropology late XX - early XXІ centuries. It is shown that the theological discourse on the merits of the man and his life unfolded within the paradigm of secular and post-secular.